Hospital Utilization and Aging in Spain (2006) - Moreno-Millan, Emilio; Molina-Morales, Agustin; Amate-Fortes, Ignacio (Current Aging Science, 2010)
Objectives: The main objective of this study is to verify the existence of a direct relation between age, ageing and hospital resources utilization. Methods: For this purpose, we use not only population variables, but also clinical parameters such as severity and complexity, as proxy of consumption and hospital costs. Through a comprehensive statistical analysis, quantitative variables of the Spanish Minimum Data Set of year 2006 (length of stay, relative weight, number of diagnoses and procedures) according to age groups and gender, types of admission (emergency or scheduled) and discharge (alive or dead), measuring the severity by weight, complications, comorbidities and mortality, and complexity by weight and length of stay. Results: The highest severity was observed in 65-69 year-old males and the highest complexity in 75-79 year-old males and 85-89 year-old females (p<.0001). The severity and complexity are also higher among 65-69 year-old males and 70- 79 year-old patients of both sexes with emergency access (p<.0001). The deceased patients are more aged with higher severity and complexity than the survivors (p<.0001). Conclusions: The age per se is not directly related to consumption of hospital resources. Therefore, aging does not necessarily imply higher consumption or increased hospital costs. Emergency admitted in-patients are older and more severe and complex than the scheduled ones, thus consuming more resources and implying higher hospital costs; the same is true for the deceased versus the survivors.
Keywords: hospital resources use